Pengaruh Arus Kas Bebas, Kepemilikan Institusional, Kebijakan Dividen, dan Ukuran Perusahaan terhadap Kebijakan Utang (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2008-2010) - Kartika Salvia (Program Magister Akuntansi Unsyiah, 2016)
The objective of this research is to examine and analyze the influence of free cash flows, institutional ownership, dividend policy, and firms size, both simultaneously and partially, toward debt policy. The research is conducted at a manufacturing company listed on the Indonesia Stock Exchange (BEI) in 2008-2010. The research type used in this research is verificative research or hypothesis testing research. The research method used in this research is census by using unbalanced panel data. Target population in this study is a manufacturing company that has complete data for all variables studied. There are 101 firm observations fulfilling the population criteria during the three years of observation. The data collection techniques using secondary data from financial statements have been audited and published www.idx.co.id. Hypothesis testing is done by multiplier linear regression method. The results of this research show that (1) free cash flow, institutional ownership, dividend policy, and firm size simultaneously have influence toward debt policy, (2) free cash flow has negatively influence toward debt policy, (3)institutional ownership has a positive influence toward debt policy, (4) dividend policy has negative influence toward debt policy, and (5) firm size has no influence toward debt policy.KEYWORDS : Free Cash Flow, Institutional Ownership, Dividend Policy, Firm Size, Debt Policy.